The diagnosis and management of atopic dermatitis - H.F. Jordaan; W.I. Visser (South African Family Practice)
The term “dermatitis” (synonym: eczema) refers to a non-infectious, inflammatory disorder of the skin. There are different forms of dermatitis including seborrhoeic dermatitis (infantile and adult types), primary irritant dermatitis, allergic contact dermatitis, dermatitis associated with venous hypertension, dyshidrotic dermatitis (synonym: idiopathic vesicular dermatitis of the hands and feet), photoallergic dermatitis, HIV-associated dermatitis, nummular dermatitis and atopic dermatitis (AD). Atopic dermatitis is common and is the only form of dermatitis that may affect virtually the entire lifespan of an individual.